2019
DOI: 10.1021/acs.orglett.9b00668
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of CF3-Substituted Spiroisochromans by [1,5]-Hydride Shift/Cyclization/Intramolecular Friedel–Crafts Reaction Sequence

Abstract: Developed herein is a diastereoselective synthesis of CF3-substituted spiroisochromans via C­(sp3)–H bond functionalization involving sequential transformations ([1,5]-hydride shift/cyclization/elimination of MeOH/intramolecular Friedel–Crafts reaction).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 82 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Then, the substrate scope of HFIP-mediated redox-neutral α-C­(sp 3 )–H etherification of o -aminobenzaldehydes for the synthesis of benzoxazines was examined, as shown in Table …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the substrate scope of HFIP-mediated redox-neutral α-C­(sp 3 )–H etherification of o -aminobenzaldehydes for the synthesis of benzoxazines was examined, as shown in Table …”
Section: Resultsmentioning
confidence: 99%
“…To target these scaffolds, the direct α-C­(sp 3 )–H functionalization of cyclic amines has proved to be an efficient way, which circumvents the prefunctionalization of amine feedstocks and streamlines the synthetic routes. , Remarkably, the cascade [1,5]-hydride transfer/cyclization has attracted considerable interest for the direct α-C­(sp 3 )–H functionalization of cyclic amines due to its inherent redox-neutral nature, environmental sustainability, and high efficiency of constructing molecular complexity and diversity (Scheme a) . By utilizing various hydride acceptors, the inert α-C­(sp 3 )–H bonds of cyclic amines are converted into C–C, C–N, and C–O bonds, thus providing access to different varieties of bioactive frameworks. Nevertheless, these transformations commonly necessitate not only the cumbersome prefabrication of substrates but also the employment of strong Lewis acids or Brønsted acids, which limit the widespread application of current hydride transfer strategy. Therefore, it is quite imperative to achieve the redox-neutral α-C­(sp 3 )–H functionalization of cyclic amines just from two independent starting materials under additive-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…While focusing on the development of sequential reactions, our group found that the combination of an internal redox reaction and intra/intermolecular Friedel-Crafts reactions was possible. 8,9 The key to achieving the sequential system was the dual role of the heteroatom (methoxy group) as (1) a driving force for the hydride shift and (2) an activator of the cyclized adduct as a leaving group. When trifluoromethyl ketones 1 having a 2-alkoxyalkyl group at the ortho-position were treated with an appropriate acid catalyst, three sequential processes (internal redox reaction/alkoxy group elimination, i.e., generation of an oxonium cation/intramolecular Friedel-Crafts reaction) proceeded smoothly to afford multi-substituted isochroman derivatives 3 in good chemical yields.…”
mentioning
confidence: 99%
“…When trifluoromethyl ketones 1 having a 2-alkoxyalkyl group at the ortho-position were treated with an appropriate acid catalyst, three sequential processes (internal redox reaction/alkoxy group elimination, i.e., generation of an oxonium cation/intramolecular Friedel-Crafts reaction) proceeded smoothly to afford multi-substituted isochroman derivatives 3 in good chemical yields. 8 The combination with intermolecular Friedel-Crafts reactions was also achieved starting from trifluoromethyl ketones having an N,N-dibenzylaminomethyl group at the ortho-position. 9 Despite the high synthetic potential, this reaction system was limited to the construction of fused heterocycles because electron donation from the oxygen atom in the ring structure provided a driving force for the elimination of heteroatoms (i.e., the generation of a carbocation).…”
mentioning
confidence: 99%
“…Recently, we have focused on developing novel molecular transformations based on intramolecular hydride shift mediated C(sp 3 )-H bond functionalizations (internal redox reaction). [16][17][18] Further investigation of this reaction system led to the discovery of a Lewis acid-catalyzed 1,3-aminomethyl migration reaction presented in the lower part of Scheme 1. a, b-Unsaturated ester 1a having a N,N-dibenzylamino group was treated with 30 mol% Sc(OTf) 3 in refluxing 1,2-dichloroethane (DCE), affording aminomethyl migration adduct 2a-not expected adduct 3-in 92% yield. The structure of the obtained adduct was confirmed by X-ray analysis.…”
mentioning
confidence: 99%